An optimal strategy for energy storage allocation in active distribution networks considering new energy consumption rates - PENG Gang; KOU Qilong; FANG Tao; GENG Xin; KONG Xiangwen; XU Yaoyao (Zhejiang dianli)
Rational allocation of energy storage not only facilitates the new energy consumption but also enables peak shaving and valley filling， ensuring the safe， reliable， and economical operation of distribution networks. This paper proposes an optimal strategy for energy storage allocation that considers new energy consumption rates， establishing a two-layer model for planning and operation. The upper layer employs a grey wolf optimizer （GWO） to determine the locations， capacities， and power ratings of energy storage， which are then passed to the lower layer as newly dispatchable energy storage resources. The lower layer uses an economical operation model for active distribution networks based on second-order cone dynamic power flow to solve the minimal total operational costs. The investment costs for energy storage are incorporated as a fitness function， providing feedback to the upper layer to guide the iterative optimization. Case studies using the modified IEEE 33-bus system demonstrate that the optimal energy storage allocation derived from the proposed strategy effectively increases the consumption rates of wind and solar energy while enhancing the overall economy of the distribution networks.